2014
DOI: 10.1080/13648470.2014.918932
|View full text |Cite
|
Sign up to set email alerts
|

The unintended consequences of sex education: an ethnography of a development intervention in Latin America

Abstract: This paper is an ethnography of a four-year, multi-disciplinary adolescent sexual and reproductive health intervention in Bolivia, Nicaragua and Ecuador. An important goal of the intervention – and of the larger global field of adolescent sexual and reproductive health – is to create more open parent-to-teen communication. This paper analyzes the project's efforts to foster such communication and how social actors variously interpreted, responded to, and repurposed the intervention's language and practices. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(25 reference statements)
0
15
0
3
Order By: Relevance
“…While unprotected sexual intercourse is the basic reason for unintended pregnancies, this individual behaviour is strongly influenced by interpersonal, institutional, social and structural level factors. These determinants are context-specific and are not always linked in a direct causal pathway to the particular health behaviour, making adolescent pregnancy, increasingly referred to as, a complex issue ( Nelson, Edmonds, Ballesteros, Encalada Soto, & Rodriguez, 2014 ). The CERCA Project took this complexity into account in its design and implementation; e.g.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…While unprotected sexual intercourse is the basic reason for unintended pregnancies, this individual behaviour is strongly influenced by interpersonal, institutional, social and structural level factors. These determinants are context-specific and are not always linked in a direct causal pathway to the particular health behaviour, making adolescent pregnancy, increasingly referred to as, a complex issue ( Nelson, Edmonds, Ballesteros, Encalada Soto, & Rodriguez, 2014 ). The CERCA Project took this complexity into account in its design and implementation; e.g.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…All of these factors shape my current analysis. The direct outcomes of the ethnographic and participatory ethnographic research were analysed and written up previously (Nelson et al 2014;Nelson and Howi 2013), but my perspective on the meanings of Project CERCA have undeniably shi ed over time. There have been a empts made by former project colleagues to rehash the successes and limitations of the community-embedded approach that CERCA sought to test (Cordova-Pozo et al 2018;Ivanova et al 2016), but my take is a diff erent one.…”
Section: Imperfect Understandingsmentioning
confidence: 99%
“…The very nature of expanding the ethnographic work to include participatory approaches created and encouraged dynamics that generated fi ction within the consensus-building aims of the project. There was no 'one' community, neither within the time-bound social world of the project itself, nor within the geographic spaces labelled and marked as sites of communityembedded intervention (Biruk and Prince 2008;Nelson et al 2014). With a background in critical analyses of sexuality education for adolescents (Ashcra 2006;Bay-Cheng 2010;Gúzman et al 2003), it was impossible not to be tuned in to how project representatives framed the 'problem' of certain adolescent sexual behaviours in moral and gendered terms or idealised certain paths to motherhood.…”
Section: Narrative Ruptures and Unsatisfactory Endingsmentioning
confidence: 99%
“…Additionally, they sought to understand the influence of family pressures, school experiences, and perceived social status on teen pregnancy. In another example, Nelson et al [ 42 ] found that in an intervention designed to promote open communication between adolescents and parents about sexual health in Latin America, some men viewed open communication about sexual behaviour as being ‘for gays and women’. This type of contextual information may not be immediately apparent in a research site but can be essential for producing a valid and comprehensive account of the acceptability and receipt of an intervention.…”
Section: Social Contextmentioning
confidence: 99%